Indonesia's Potential to Build Nuclear Energy in Geopolitical Perspective - Muslikhatin, Lilik; Yusuf, Rizal; Golan, Suhara; Shobri, Taufiq; H R, Wildan Akbar; Murfi, Yudhi; Midhio, I Wayan; Yusgiantoro, Purnomo (Technium Social Sciences Journal, 2024)
The use of nuclear weapons in armed conflict has become a major focus in today's geopolitical world. With growing tensions between major powers and ongoing regional conflicts, the debate over the use of nuclear weapons is increasingly heated. In the midst of this global context, Indonesia, as an active member of ASEAN which consistently promotes peace and stability in the region, is faced with major challenges related to the use of nuclear weapons in international conflicts. In this context, the research in this journal aims to examine Indonesia's policies in dealing with the use of weapons. nuclear power in a growing international conflict. This research uses the theories of Situational Leadership and Transformational Leadership to understand Indonesia's potential in developing nuclear weapons. The approach used is qualitative involving in-depth interviews, document analysis, and participant observation. A phenomenological approach is used to understand subjective interpretations from the experts' point of view. The Hierarchical Process Analysis (AHP) data processing method is used to analyze data and support decision making. and it was concluded that Indonesia had no interest or intention to develop or produce nuclear weapons. Political factors, international law, and commitment to world peace provide a strong basis for this country in rejecting the option of developing nuclear weapons.